2023
DOI: 10.1021/acsapm.3c00629
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin-Based Degradable Polyurethane Thermosets Demonstrating High Bio-Content and Mechanical Properties

Abstract: Polyurethanes are widely used polymeric materials, but they are rarely biorenewable and degradable. Although some previously reported bio-based polyurethanes exhibit good thermal and mechanical properties, their bio-content is usually low, resulting from the only replacement of the diol monomer instead of the whole diol/diisocyanate pairs. In addition, traditional polyurethanes are often difficult to degrade, leading to environmental issues. To address these issues, we propose a solution by sourcing both the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The Fourier transform infrared (FT-IR) spectra of vanillin, DOPO, and VDP are shown in Figure a: the absorption peaks at 3100–3500 and 1662 cm –1 belong to the characteristic peaks of −OH and the CO stretching vibration, respectively, while the peak at 2437 cm –1 is associated with the P–H bond on DOPO. , In the VDP spectrum, it can be observed that both the CO stretching vibration and P–H characteristic peaks disappeared, while characteristic peaks at 1604 cm –1 (P–C bond), 1270 cm –1 (C–N bond), 1231 cm –1 (PO bond), and 916 cm –1 (P–O bond) appeared. , The FT-IR spectra of the synthesized polyurethanes are shown in Figure b. The peaks at 3360 and 1725 cm –1 correspond to the N–H and CO stretching vibrations of the polyurethanes, respectively, and the peaks at 2941 and 2854 cm –1 are attributed to the C–H stretching vibrations of −CH 3 and −CH 2 , respectively . The peaks at 1529 and 1153 cm –1 correspond to the C–N and C–O–C stretching vibrations, and the disappearance of the NCO stretching vibration peak at 2261 cm –1 proves that all NCO groups on HDI were consumed. , After the addition of VDP, a urethane stretching vibration peak appeared at 1681 cm –1 , and the peak was significantly enhanced, which proved that the synthesized VDP successfully reacted with the −NCO groups of HDI.…”
Section: Resultsmentioning
confidence: 99%
“…The Fourier transform infrared (FT-IR) spectra of vanillin, DOPO, and VDP are shown in Figure a: the absorption peaks at 3100–3500 and 1662 cm –1 belong to the characteristic peaks of −OH and the CO stretching vibration, respectively, while the peak at 2437 cm –1 is associated with the P–H bond on DOPO. , In the VDP spectrum, it can be observed that both the CO stretching vibration and P–H characteristic peaks disappeared, while characteristic peaks at 1604 cm –1 (P–C bond), 1270 cm –1 (C–N bond), 1231 cm –1 (PO bond), and 916 cm –1 (P–O bond) appeared. , The FT-IR spectra of the synthesized polyurethanes are shown in Figure b. The peaks at 3360 and 1725 cm –1 correspond to the N–H and CO stretching vibrations of the polyurethanes, respectively, and the peaks at 2941 and 2854 cm –1 are attributed to the C–H stretching vibrations of −CH 3 and −CH 2 , respectively . The peaks at 1529 and 1153 cm –1 correspond to the C–N and C–O–C stretching vibrations, and the disappearance of the NCO stretching vibration peak at 2261 cm –1 proves that all NCO groups on HDI were consumed. , After the addition of VDP, a urethane stretching vibration peak appeared at 1681 cm –1 , and the peak was significantly enhanced, which proved that the synthesized VDP successfully reacted with the −NCO groups of HDI.…”
Section: Resultsmentioning
confidence: 99%
“…11, the PU networks produced in this work exhibited comparable or higher tensile strength and elongation at break than most biobased PU thermosets reported in the literature or non-renewable commercially available crosslinked polyurethanes. 3,6,48–59 The attractive features of the developed PU thermosets such as good and easily tunable mechanical performance, including a very broad range of elongation at break (15–188%), Young's moduli (6.1–648.8 MPa) and tensile strength (3.3–31.1 MPa), together with their high heat resistance and good optical transparency could cement these PUs as a promising class of high-performance amorphous polyurethane materials.…”
Section: Resultsmentioning
confidence: 99%
“…3 Additionally, conventional PU thermosets that account for 31% of the thermoset market 4 are not easily biodegraded or recycled due to their permanent crosslinked structures, which can escalate their adverse environmental impact. 3 With increasing reliance on PUs and in response to the growing awareness of global challenges related to dwindling fossil resources, greenhouse gas emissions, environmental pollution and surging energy demand, 5 much work has been devoted to the development of more environmentally friendly PUs with reduced carbon footprint. 3,6–17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many stimulus conditions contributing to adhesive debonding have been studied, including optical, thermal, magnetic, electrical, chemical, etc. Light can induce polymer degradation, isomerization, , or overcuring, heat can induce decomposition, , expansion, rearrangement, , and phase separation to achieve debonding.…”
Section: Introductionmentioning
confidence: 99%